THE IMPACT OF SPOTIFY ON IMPROVING STUDENTS' LISTENING SKILLS: SYSTEMATIC LITERATURE REVIEW - Muna Mawaddah; Muhammad Dewa Prasetya; Rizki Bobi Baihaki; Naf’an Tarihoran (PT. Intelek Cendikiawan Nusantara, 2025)
Spotify is one of the world's most popular digital audio streaming platforms, offering millions of songs and podcasts that are easily accessible and flexible. Building on this potential, his study aims to investigate the impact of using the Spotify application on students' English listening skills, as well as identify the main benefits and challenges of its implementation. This research adopts a systematic literature review design (Systematic Literature Review) by analyzing empirical studies published within the context of English as a Foreign Language (EFL) instruction. The review findings show that using Spotify significantly improves listening comprehension (as indicated by a substantial rise in test scores) and is perceived by students as a motivating medium that effectively reduces learning anxiety. However, the identified challenges include unstable internet connections and overly fast speech rates in the audio material. It is concluded that Spotify is a highly effective digital tool for developing listening skills as it bridges students' digital habits with academic needs. The implication is that educators should integrate this platform as a source of authentic language input while designing supportive strategies to overcome technical constraints and select appropriate audio content.